Taphonomic analysis of Pseudalopex griseus (Gray, 1837) scat assemblages and their archaeological implications - Gómez, Gustavo Norberto (2007)
Grey fox (Pseudalopex griseus) scats deposited in the immediate vicinity of guanaco (Lama guanicoe) carcasses were analyzed to evaluate this carnivore´s transport of bones. Samples were from the arid, semi-desert Río Negro Province, Argentina, where the annual mean temperature (15ºC) varies widely with the season. Rates of breakage, the presence of tooth marks and digestion traces on bones from scats were analyzed to categorize the taphonomic signature of the small grey fox. The values of the modification variables used in the categorization indicate that the grey fox (Pseudalopex griseus) may be considered a Category 5 predator.